Nitrogen-Fixing Activity of Root Nodules in Relation to Their Size in Peanut (Arachis hypogaea L.) - Ryosuke Tajima; O New Lee; Jun Abe; Alexander Lux; Shigenori Morita (Plant Production Science, 2007)
The nitrogen-fixing activity of root nodules was examined with reference to the nodule size in peanut. Root nodules of field-grown peanut were collected at flowering through harvesting stages and classified into five groups of size using a circle template. Then acetylene reduction activity was measured to evaluate nitrogen-fixing activity for respective size groups. In addition, the diameter of the cross-section of each root nodule and rhizobium-infected areas on the cross-section were measured. The results showed that the nitrogen-fixing activity of root nodules is closely related with their size. In the root nodules in the medium size group (1.5− 2.0 mm in diameter), nitrogen-fixing activity per unit fresh weight of nodule was highest at the flowering stage and rapidly decreased thereafter. The nitrogen-fixing activity of root nodules larger than 2.0 mm in diameter did not vary significantly with their size. Colors of rhizobium-infected zones varied with their size: white in small nodules; red in medium-sized nodules; and greenish in larger nodules, which suggests that the concentration of leghemoglobin is highest in the medium-sized nodules. Nitrogen-fixing activities of the medium-sized nodules might determine the amount of nitrogen fixation in the whole root system during pod-filling because medium-sized nodules had high activity and were large in number. Classification of root-nodule size based on the circle template is a simple, rapid, and useful method to evaluate nitrogen-fixing activity of root nodules.